Maximum growth rates and possible life strategies of different bacterioplankton groups in relation to phosphorus availability in a freshwater reservoir - Simek, Karel; Hornák, Karel; Jezbera, Jan; Nedoma, Jirí; Vrba, Jaroslav; Straskrábová, Viera; Macek, Miroslav; Dolan, John R; Hahn, Martin W (Environmental microbiology, 2006)
We investigated net growth rates of distinct bacterioplankton groups and heterotrophic nanoflagellate (HNF) communities in relation to phosphorus availability by analysing eight in situ manipulation experiments, conducted between 1997 and 2003, in the canyon-shaped Rímov reservoir (Czech Republic). Water samples were size-fractionated and incubated in dialysis bags at the sampling site or transplanted into an area of the reservoir, which differed in phosphorus limitation (range of soluble reactive phosphorus concentrations--SRP, 0.7-96 microg l-1). Using five different rRNA-targeted oligonucleotide probes, net growth rates of the probe-defined bacterial groups and HNF assemblages were estimated and related to SRP using Monod kinetics, yielding growth rate constants specific for each bacterial group. We found highly significant differences among their maximum growth rates while insignificant differences were detected in the saturation constants. However, the latter constants represent only tentative estimates mainly due to insufficient sensitivity of the method used at low in situ SRP concentrations. Interestingly, in these same experiments HNF assemblages grew significantly faster than any bacterial group studied except for a small, but abundant cluster of Betaproteobacteria (targeted by the R-BT065 probe). Potential ecological implications of different growth capabilities for possible life strategies of different bacterial phylogenetic lineages are discussed.
Keywords: oligonukleotidové sondy; Colony Count, Microbial; Ecosystem; hybridizace in situ fluorescenční; fosfor; RNA, Ribosomal, 16S; Eukaryota; Bacteria; počet mikrobiálních kolonií; sladká voda; Fresh Water; Plankton; plankton; Oligonucleotide Probes; kinetika; Animals; zvířata; ekosystém; RNA ribozomální 16S; In Situ Hybridization, Fluorescence; Kinetics; Phosphorus